Gene therapy of rare diseases as a milestone in medicine - overview of the field and report on initial experiences in Slovenia - Urh Grošelj; Marko Kavčič; Ana Drole Torkar; Jan Kafol; Duško Lainšček; Roman Jerala; Matjaž Sever; Samo Zver; Gregor Serša; Maja Čemažar; Primož Strojan; Aleš Grošelj; et al. (Orphanet Journal of Rare Diseases)
Abstract Gene therapy has transitioned from a long-awaited promise to a clinical reality, offering transformative treatments for rare congenital diseases and certain cancers, which have a significant impact on patients’ lives. Current approaches focus on gene replacement therapy, either in vivo or ex vivo, mostly utilizing viral vectors to deliver therapeutic genes into target cells. However, refining these techniques is essential to overcome challenges and complications associated with gene therapy to ensure long-term safety and efficacy. Slovenia has witnessed significant advancements in this field since 2018, marked by successful gene therapy trials and treatments for various rare diseases. Significant strides have been made in the field of gene therapy in Slovenia, treating patients with spinal muscular atrophy and rare metabolic disorders, including the pioneering work on CTNNB1 syndrome. Additionally, immune gene therapy, exemplified by IL-12 adjuvant therapy for cancer, has been a focus of research in Slovenia. Through patient-centred initiatives and international collaborations, researchers in Slovenia are advancing preclinical research and clinical trials, paving the way for accessible gene therapies. Establishing clinical infrastructure and genomic diagnostics for rare diseases is crucial for gene therapy implementation. Efforts in this regard in Slovenia, including the establishment of a Centre for Rare Diseases, Centre for the Technologies of Gene and Cell Therapy, and rapid genomic diagnostics, demonstrate a commitment to comprehensive patient care. Despite the promises of gene therapy, challenges remain, including cost, distribution, efficacy, and long-term safety. Collaborative efforts are essential to address these challenges and ensure equitable access to innovative therapies for patients with rare diseases.